Toxicity of crude rhizome extract of Kaempferia galanga L. (Proh Hom) - Kanjanapothi D. (2014)
The ethanolic rhizome extract of Kaempferia galanga L. (Zingiberaceae) was studied by conventional pharmacological methods including the Hippocratic screening test, and acute and subacute toxicities in rats. The hexane fraction was tested for dermal irritation in rabbits. The ethanolic extract, when tested by the Hippocratic screening test, demonstrated signs that indicated CNS depression such as a decrease in motor activity and respiratory rate, and a loss of screen grip and analgesia. In the acute toxicity test, oral administration of 5g/kg of Kaempferia galanga produced neither mortality nor significant differences in the body and organ weights between controls and treated animals. Moreover, both gross abnormalities and histopathological changes were not comparatively detectable between all controls and treated animals of both sexes. In subacute toxicity studies, no mortality was observed when varying doses of 25, 50 or 100mg/kg of ethanolic Kaempferia galanga extract were administered orally per day for a period of 28 days. There were no significant differences in the body and organ weights between controls and treated animals of both sexes. Hematological analysis showed no differences in any of the parameters examined (WBC count, platelet, hematocrit and hemoglobin estimation) in either the control or treated groups of both sexes. However, the differential leukocyte counts showed a slight but significant decrease of lymphocyte count in the 50 and 100mg/kg male rat groups. In the blood chemistry analysis, no significant change occurred in the blood chemistry parameters, including glucose, creatinine, blood urea nitrogen (BUN), aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (Alk-P), total protein and albumin of both sexes. Pathologically, neither gross abnormalities nor histopathological changes were observed. No sign of irritation was observed during the dermal irritation test of the hexane fraction of Kaempferia galanga. © 2003 Elsevier Ireland Ltd. All rights reserved.